Elucidating the Distribution and Speciation of Boron and Cesium in BCsX Zeolite Catalysts for Styrene Production. Issue 4 (4th December 2017) - Martín, Antonio J.; Mitchell, Sharon; Scholder, Olivier; Verel, René; Hauert, Roland; Bernard, Laetitia; Jensen, Christopher; Schwefer, Meinhard; Pérez‐Ramírez, Javier
Abstract: An improved understanding of the nature and distribution of boron and cesium species in BCsX zeolites is a prerequisite to guide future developments in the environmentally attractive, yet challenging, production of styrene through the side‐chain alkylation of toluene with methanol. Herein, standard characterization and catalytic tests are complemented by integrated visualization through time‐of‐flight secondary‐ion mass spectrometry and energy‐dispersive X‐ray spectroscopy and detailed assessment by 133 Cs and 11 B NMR spectroscopy, to correlate the properties and performance during successive ion‐exchange and impregnation steps in the preparation of both powders and millimeter‐sized granules. The results highlight a significant impact of catalyst scaleup on the effective introduction of boron species, which originates chemical heterogeneity that is linked to selectivity losses. They also illustrate the complexity of elucidating the role of this promotor, which interacts with cesium cations and exhibits different coordination states and chemical environments, depending on the pretreatment. Abstract : Location, location, location ! The distribution and speciation of boron and cesium in boron‐promoted cesium‐exchanged zeolite X, which is the reference catalyst for styrene production through the alkylation of toluene with methanol, is assessed (see figure). The results reveal that boron is present in different chemical and coordination environments, and its effective introduction is affected by catalyst scaleup.